Varslingsklokken Berte Kanutte Aarflot - bondekone og vekkerrøst - Aarflot, Andreas (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
Berte Kanutte Aarflot lived in the Northwestern region of Norway in the 19th century. In this book, her great-great-grandson gives the first overview of her written work and puts it in the context of her time. Aarflot, a woman who left a big mark both in the religious sphere and in society, published over 600 pages of religious litterature. This is the 34th book in the series Kyrkjefag Profil.